2016
DOI: 10.1007/s00011-016-0928-z
|View full text |Cite
|
Sign up to set email alerts
|

The infrapatellar fat pad is affected by injury induced inflammation in the rabbit knee: use of dexamethasone to mitigate damage

Abstract: One IA administration of a glucocorticoid appears to mitigate the initial inflammation within the joint, but is not sufficient to protect the joint to 9 weeks post-surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Exposure to post‐surgical inflammation can compromise synovial stem cells, thus potentially affecting their ability to contribute to endogenous repair post‐injury . We have also assessed the IPFP and observed a distinct inflammatory response (with increased cellularity and early fibrosis) at both 48 hours and 9 weeks post‐surgery, thereby suggesting that this tissue is effected by, and potentially contributes to a compromised joint environment.…”
Section: Biological Alterations Associated With Joint Injurymentioning
confidence: 90%
“…Exposure to post‐surgical inflammation can compromise synovial stem cells, thus potentially affecting their ability to contribute to endogenous repair post‐injury . We have also assessed the IPFP and observed a distinct inflammatory response (with increased cellularity and early fibrosis) at both 48 hours and 9 weeks post‐surgery, thereby suggesting that this tissue is effected by, and potentially contributes to a compromised joint environment.…”
Section: Biological Alterations Associated With Joint Injurymentioning
confidence: 90%
“…According to many research studies in murine models of OA, suppression of VEGF expression may be considered as an interesting potential therapy to treat this disabling disease [121, 123]. Previously, also Heard et al tried to identify and approach to counteract joint inflammation in OA [124]. Interestingly, the authors considered the IFP as a target; in fact, they tried to mitigate damage descending from IFP injury administering dexamethasone to rabbits used as a model of surgically induced knee injury and inflammation.…”
Section: Ifp-synovial Membrane Mediators Involved In Oa Pathology mentioning
confidence: 99%
“…The second study [20■] reported similar infiltration in the infrapatellar fat pad (IFP). IFP inflammation is reported in animal models of joint injury and osteoarthritis [21], so future investigation of the underlying mechanisms and consequences should be forthcoming.…”
Section: Local Infiltration Of Cellsmentioning
confidence: 99%